2004
DOI: 10.1002/pssb.200405032
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterization of InAsN single quantum wells grown by RF‐MBE

Abstract: InAsN/GaAs single quantum wells (SQWs) were fabricated on semi insulating GaAs(001) substrates by RF-MBE. The redshift of photoluminescence peak with increasing nitrogen content was observed. It is contrary to the recent report for the bulk dilute InAsN alloy where the blueshift of absorption edge has occurred predominantly due to the Burstein-Moss effect. Considering that the Burstein-Moss shift energy of the one-dimensional quantum well is significantly lower than that of the bulk, this redshift of photolumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…For comparison, we also show some results from absorption measurements published previously by other groups. [8][9][10] The dashed curve shows the theoretical be-…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For comparison, we also show some results from absorption measurements published previously by other groups. [8][9][10] The dashed curve shows the theoretical be-…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Such effects have, indeed, proven extremely problematic in previous attempts to measure band gap reduction directly in InNAs using absorption spectroscopy, with large blueshifts being observed rather than any redshift. [6][7][8][9] The Moss-Burstein shifts were "subtracted" during analysis to infer a net redshift in band gap. [7][8][9] An unambiguous redshift of the absorption edge of InNAs alloys with increasing nitrogen content has been seen only in one previous study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, we avoided N flux in the growth of the wetting layer. For the growth of the InAsN QDs, the rf power and the N 2 flow rate were 175 W and 0.50 sccm, which gave x = 0.02 in a bulk InAs 1-x N x layer [3,4]. For reducing the N supply by half, the N 2 flow was allowed intermittently by 1-sec-duration and 50%-duty pulses.…”
Section: Methodsmentioning
confidence: 99%
“…The same thing may be expected in the QDs, giving a red-shift of emission spectra. In fact, the bandgap reduction of the InAsN alloy is estimated as ~40 meV with 1%-N incorporation [4,5]. It has also been shown that N can be incorporated into InAs up to ~5 % in spite of the extremely low equilibrium solubility [5].…”
Section: Introductionmentioning
confidence: 98%